2017
DOI: 10.3389/fmicb.2017.01866
|View full text |Cite
|
Sign up to set email alerts
|

Regulation-Structured Dynamic Metabolic Model Provides a Potential Mechanism for Delayed Enzyme Response in Denitrification Process

Abstract: In a recent study of denitrification dynamics in hyporheic zone sediments, we observed a significant time lag (up to several days) in enzymatic response to the changes in substrate concentration. To explore an underlying mechanism and understand the interactive dynamics between enzymes and nutrients, we developed a trait-based model that associates a community's traits with functional enzymes, instead of typically used species guilds (or functional guilds). This enzyme-based formulation allows to collectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…The effectiveness of the cybernetic modeling was successfully demonstrated in previous case studies of modeling denitrifying organisms (Song & Liu, ) and microbial communities (Song et al, ). In the present work, we used a simplified version of the cybernetic model developed by Song et al () for linking microbial communities with enzyme expression observed in a denitrification experiment (Li et al, ). The supporting information provides more details on the derivation of the simplified cybernetic model (Text S1).…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of the cybernetic modeling was successfully demonstrated in previous case studies of modeling denitrifying organisms (Song & Liu, ) and microbial communities (Song et al, ). In the present work, we used a simplified version of the cybernetic model developed by Song et al () for linking microbial communities with enzyme expression observed in a denitrification experiment (Li et al, ). The supporting information provides more details on the derivation of the simplified cybernetic model (Text S1).…”
Section: Methodsmentioning
confidence: 99%
“…The biogeochemical reaction network and the reaction rates in the model were adopted from the work of Li et al () and H.‐S. Song et al (). The reactions of oxidative respiration and denitrification for the dissolved organic carbon (CH 2 O) and the synthesis of biomass (C 5 H 7 O 2 N) were considered as follows: lefttrueCH2O+normalO2=CO2+normalH2OCH2O+2NO3=2NO2+CO2+normalH2OCH2O+4/3NO2+4/3normalH+=2/3normalN2+CO2+5/3normalH2OCH2O+1/5NH4+=1/5normalC5normalH7normalO2N+3/5normalH2O+1/5normalH+. …”
Section: Implementation Of Groundwater Biogeochemical Reactive Transportmentioning
confidence: 99%
“…Temperature‐dependent reaction rate, r i , is defined using the Arrhenius equation, that is, ri=rbase,iexp[]EaR()1T126+273.15,i=1,2,3, where r i is the reaction rate under temperature T (in Kelvin) with subscript i being the generic reaction index, E a is the activation energy (0.65 ev in this study), R is the gas constant (8.314 J·mol −1 ·K −1 ), and r base, i is the base rate derived from laboratory batch experiments (under the room temperature of 26 °C). After incorporating microbial regulation term into the Monod kinetics, the base rate, r base, i , is defined by rbase,ikin=eirelkidiKd,i+diaiKa,i+ai,1emi=1,2,3, where the relative enzyme levels, eirel=rikin/j=13rjkin, regulate the rates of oxidative respiration and denitrification reactions (H. Song et al, ), k i (mol·L −1 ·day −1 ) is the maximum specific uptake rate of organic carbon (CH 2 O), a i (mol/L) is the electron acceptor concentration, d i (mol/L) is the electron donor concentration, and K a , i (mol/L) and K d , i (mol/L) are the half‐saturation constants for electron acceptors and electron donors, respectively. More details about the reaction network and rates can be found in X.…”
Section: Implementation Of Groundwater Biogeochemical Reactive Transportmentioning
confidence: 99%
See 2 more Smart Citations